Simultaneous determination of abamectin homologs H 2 B 1a and H 2 B 1b in gel formulation by high performance liquid chromatography (Brazilian Journal of Pharmaceutical Sciences, 2016)
Abamectin is a drug with antiparasitic properties used in several pharmaceutical formulations. The objective of this research was to develop and validate a high performance liquid chromatographic (HPLC) method for quantification of the two abamectin homologs (H2B1a and H2B1b) in gel formulation. This HPLC method was validated using a LichroCart(r) 100 RP-18 (125 x 4 mm, 5 µm) column. The mobile phase contained of acetonitrile and water (95:5 v/v) with 1% acetic acid. The flow rate was 1.0 mL min-1 and UV detection was performed at 245 nm. Mobile phase solutions were prepared containing a nominal concentration 185.2 µg mL-1 H2B1a and 9.6 µg mL-1 H2B1b. The method displayed good linearity in the concentration range of 148.1 - 222.3 µg mL-1 and 7.7 - 11.5 µg mL-1, for H2B1a and H2B1b, respectively, with a correlation coefficient of (r)>; 0.99 for both compounds, calculated by the least mean squares method. Detection limits (DLs) were 2.8 µg mL-1 and 1.2 µg mL-1 and quantitation limits (QLs) were 8.6 µg mL-1 and 3.8 µg mL-1, for H2B1a and H2B1b, respectively. The method is simple, economical and efficient for the quantitative determination of abamectin H2B1a and H2B1b homologs in pharmaceutical preparations.